Hippolyte Leon Denizard Rivail, ou Allan Kardec : um professor pestalozziano na França do tempo das revoluções - Brettas, Anderson Claytom Ferreira (2013)
French Spiritualism is relatively disseminated in Brazil - creed professed by about two percent of the population, about four million declared adherents - but whose categories, such as the belief in the immortality of the soul, in the reincarnation and in the possibility of contact with the dead, are disseminated in the national culture, shared to some extent by adherents of all religions. Moreover, the biographical and intellectual aspects of the figure of Allan Kardec, founder of the spiritualist doctrine, although it is a popular name, are little known, especially in academic production. Allan Kardec is the pseudonym of Hippolyte Leon Denizard Rivail (1804/1869), teacher, pedagogue, writer of textbooks, founder and director of schools in France. He studied with one of the most influential names in the contemporary pedagogy, Swiss-German Johann Heinrich Pestalozzi (1746/1827), in the school installed in the castle of Yverdon, Switzerland, and he became a disciple and propagandists of the liberal and democratic ideas of the education. This thesis analyzes the historical context of the nineteenth century, permeated by political upheaval as a consequence of the French Revolution, by the emergence of urban and industrial society, by the spread of the categories of modern scientific thought, as scientism and evolutionism, and the developments in the activities of Denizard Rivail, as an educator, then as a developer of spiritualist doctrine. The central idea of the thesis is the link between the pedagogical ideas of Pestalozzi and the systematization of the spiritualist doctrine, presented as science, philosophy and religion. The esotericism was relatively popular at the time, and one episode is paradigmatic in the history of modern spiritualism - known as \"the case of the Fox sisters,\" in which was established through codes an alleged communication with a death in the family home. The event had repercussion and the other side of the Atlantic, in Europe in process of consolidation of the bourgeois modernity, the called turning tables became fashionable, whose sessions with the alleged contact with unseen forces cheered the halls of social circles. Denizard Rivail, who retired from the educational activities because of dissatisfaction with the direction of the policy of Louis Napoleon, whose coup in 1851 foiled the political utopias of revolutionary France and installed the Second French Empire (1852/1870), in an arrangement that had the support of the haute bourgeoisie, aristocratic sectors and the Catholic Church - he became interested in the study of the turning tables, and sought to extend the reason and the scientific logic in those studies. The adoption of the pseudonym Allan Kardec marks this inflection in his life. Scholars from various fields such as physics, astronomy, medicine, among others, have engaged in such research, but the humanism of Allan Kardec seized by the influences of education, especially of Pestalozzi, contributed to the creation of Spiritualism as it is known, with emphasis on human advancement.